The universal approach for facilitating participation, tool-use learning and application of the ALP-facilitating strategies : (Instructional course, 45 min) - Nilsson, Lisbeth ; 0000-0001-5988-3192 (Oceania Seating Symposium, Rotorua, New Zealand, 2025-11-04 - 2025-11-06, 2025)
Dr Lisbeth Nilsson Learning objectives: 1. Describe at least three essential aspects of the facilitating approach. 2. Explain why these aspects can facilitate optimal outcomes of intervention. 3. Evaluate usefulness of the universal facilitating approach in your own practice. Session description: The process of learning joystick-use and training strategies for each phase in the process were identified in the Driving to Learn project, where children and adults with profound cognitive disabilities got the opportunity to practice in a powered wheelchair. In collaboration with Josephine Durkin the findings were further developed into the ALP-tool, including instrument and facilitating strategies. Moreover, Nilsson and Durkin compared their views on how to interact in an intervention situation to enable optimal outcomes. Their elaborations led to the identification of a facilitating approach for learning to use powered mobility devices. Thereafter the approach has been advanced, in collaboration with a variety of professionals, through the application of the ALP in different situations of activity, participation and use of assistive technologies. The universal facilitating approach is intended to be used across all eight phases in the learning process. It is focused on inter-personal skills necessary to establish a safe and secure relationship based on mutual interaction and communication. The most essential aspects of the approach are strongly related to presence of motivation, endurance, responsiveness, adaptability, usefulness and predictability in both/all partakers in a learning situation or context. As the facilitating approach concerns qualitative aspects of interaction it can be applied to any situation where a learning process needs facilitation. Its application is independent of age, mental or physical abilities, situation of activity or participation or type of tool to be used. Content references: 1. Nilsson, L. (2007). Driving to Learn: the process of growing consciousness of tool use: a grounded theory of de-plateauing (Publication Number 2007:34) [Doctoral dissertation, Lund University]. Lund, Sweden. https://www.researchgate.net/publication/233819998_Driving_to_Learn_The_process_of_growing_consciousness_of_tool_use-a_grounded_theory_of_de-plateauing 2. Nilsson, L., & Durkin, J. (2014). Assessment of learning powered mobility use - Applying grounded theory to occupational performance. Journal of Rehabilitation Research and Development, 51(6), 963-974. https://doi.org/10.1682/JRRD.2013.11.0237 3. Nilsson, L., & Durkin, J. (2017). Powered mobility intervention: understanding the position of tool use learning as part of implementing the ALP tool. Disability and Rehabilitation: Assistive Technology, 12(7), 730-739. https://doi.org/10.1080/17483107.2016.1253119 4. Nilsson, L. (n.d.). Driving to Learn/ALP-tool. Guide for application of the ALP-tool (universal, version 2.0 and ALP for AAC), PDF. Download at https://www.lisbethnilsson.se/en/alp-tool/ Presenter biography: Lisbeth Nilsson is a PhD, Occupational Therapist and specialist, associated to Department of Health Sciences, Lund University, Sweden. She developed the Driving to Learn intervention for people with profound cognitive disabilities (1996-2007). She and Josephine Durkin, UK, collaborated on developing the Assessment of Powered mobility use (ALP) (2009-2016). Her special interests are how infants, children and adults with cognitive disabilities learn how to use a variety of tools, and how to assess and facilitate the learning process. Her current focus is explaining how to apply the universal ALP tool for assessment and facilitation of learning in a variety of tool-use interventions. Her ongoing research collaborations nationally and internationally involves OTs, PTs and other rehabilitation professionals.
Keywords: universal assessment; aeesessment of learning process; facilitation of learning